Environmentally Friendly Synthesis, Antibacterial Activity, and Photocatalytic Performance of AG Nanoparticles Made from Leucaena Leucocephala Leaves Extract - Karrar Hazim, Ghusoon Faidhi Hameed, Lidia Mohamed, Faris j. Alyasiri (Pakistan Journal of Medical & Health Sciences, 2022)
The leaf extract of the plant Leucaena leucocephala was used in this research to synthesize environmentally-friendly nanotechnologies. This environmentally friendly procedure is completely safe and non-toxic. The approach is cost-effective, simple to use, and effective, and the attributes of the resultant compounds can be regulated. For example, the Ag compound can be controlled using the same plant extract and reaction. The findings and properties of these nanoparticles were investigated using a variety of techniques, including field emission-scanning electron microscopy (FE-SEM), X-ray diffraction (XRD), and atomic force microscopy (AFM). EDX-mapping was also used to explore the analysis of Ag NPs. Electron microscopy investigations with transmission electron microscopes (TEM). which indicated the presence of Ag in the compound and their effective degradation. The produced chemical was tested for effectiveness using bacteria. The antibacterial activity of Ag NPs was investigated utilizing two different species of bacteria, Gram-negative E. Coli and Gram-positive S.aureus e.In addition, the photocatalytic capacity of Ag NPs was discovered through the photodegradation of dyes, as the rhodamine B dye was decomposed at a 78% percent rate. The effect of the catalyst amount and amounts (0.2,0.4,0.6,0.8,1, 1.2,1.4,1.6g/L) were investigated, with the best weight being 1gm and the dye concentration being 10ppm. Water and oxygen are converted to.OH radical with very powerful oxidation by receivers for electrons as well as those electrons and free holes.